2008
DOI: 10.1007/s00417-008-0976-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of bevacizumab on angiogenesis and corneal neovascularization

Abstract: Bevacizumab effectively inhibits angiogenesis and corneal neovascularization, and could be used as a inhibitor of corneal neovascularization in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 18 publications
2
20
0
2
Order By: Relevance
“…In vivo observation on days 7 and 21, however, revealed more vessels with visible flow than were visible in high magnification photographs. Consequently, in vivo imaging may be a more sensitive method to assess active vessel presence in the cornea after therapy than current methods using photography [16,17,22,28,30] or flourescein angiography [10,26,29,31]. At day 21, some persistent vessels were found in the cornea in all groups, and likely reflected their maturity as confirmed by perivascular NG2 staining in this study, and earlier findings of αSMA+NG2+ cells lining vessels 7 days after stimulus in our model [33].…”
Section: In Vivo Imaging Of Human Corneal Capillary Regression: Reporsupporting
confidence: 75%
See 1 more Smart Citation
“…In vivo observation on days 7 and 21, however, revealed more vessels with visible flow than were visible in high magnification photographs. Consequently, in vivo imaging may be a more sensitive method to assess active vessel presence in the cornea after therapy than current methods using photography [16,17,22,28,30] or flourescein angiography [10,26,29,31]. At day 21, some persistent vessels were found in the cornea in all groups, and likely reflected their maturity as confirmed by perivascular NG2 staining in this study, and earlier findings of αSMA+NG2+ cells lining vessels 7 days after stimulus in our model [33].…”
Section: In Vivo Imaging Of Human Corneal Capillary Regression: Reporsupporting
confidence: 75%
“…In both clinical and experimental studies, corneal capillary regression is commonly evaluated by degree of vascular invasion at the tissue level, using photography of visible blood vessels, fluorescein angiography, or by immunostaining of vascular endothelium at fixed time points [17,[21][22][23][24][25][26][27][28][29][30][31][32]. Little, however, is known about the morphologic characteristics of regressing capillaries at the cellular level following therapy.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 In addition, bevacizumab was demonstrated to reduce VEGF-induced permeability and proliferation of cultured porcine choroidal endothelial cells, 18 inhibit VEGF-stimulated proliferation of monkey choroidal endothelial cells, 33 and inhibit VEGF-induced migration of HUVEC. 36 In contrast to these studies, bevacizumab was shown to have a stimulatory effect on cell proliferation in the rat retinal ganglion cell line RGC-5, which was suggested to be due to a nonspecific effect via increasing the protein contents of the cell growth environment. 37 Since 2009, there have been increasing number of studies that have compared the properties of ranibizumab and bevacizumab and investigated their impact on physiological retinal cell functioning.…”
mentioning
confidence: 73%
“…Han et al [29] investigated the inhibitory effect of subconjunctival bevacizumab on CNV by means of subconjunctival injection of 25 mg/ml bevacizumab after corneal chemical burn injury. On days 3 and 8 after the subconjunctival injection, bevacizumab-treated eyes showed Color version available online less neovascular growth than eyes treated with balanced salt solution.…”
Section: Discussionmentioning
confidence: 99%